Faktor-Faktor yang Memengaruhi Ketepatan Waktu Pelaporan Keuangan Perusahaan Perbankan yang Terdaftar pada BEI Periode 2017-2021 - Muhlisin Ahady; Agus Khazin Fauzi; Putri Reno Kemala sari (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
The era of economic globalization which has changed the behavior of the business world has influenced the development of the Indonesian economy, especially the banking industry sector. This research aims to determine the effect of profitability, leverage, company size and audit opinion on the timeliness of company financial reporting. The population in this research are banking companies listed on the Indonesia Stock Exchange in 2017-2021 with a sampling technique using purposive sampling. The data analysis technique used in this research uses multiple linear regression analysis with SPSS Version 23. The results of this study show that partially Profitability has an effect on timeliness of financial reporting, Leverage has no effect on timeliness of financial reporting, company size has an effect on timeliness of financial reporting, while the audit opinion has no effect on the timeliness of financial reporting. The results of this research also show that the independent variables, namely profitability, leverage, company size and audit opinion, are able to influence the dependent variable, namely the timeliness of financial reporting, by 0.225 or 22.5%, while the remaining 77.5% is influenced by other variables not used in this research.